Entrepreneurial Opportunities : Economics and Sustainability for Future Growth. - Ratten, Vanessa (Emerald Publishing Limited, 2020)
Focusing on sustainable innovation in emerging economies, this book characterises and responds to contemporary market pressures felt by business leaders worldwide. The book offers new ways of looking at entrepreneurial opportunities in a range of contexts, including emerging markets, franchise relationships, revenue management, and tourism.